EKSTRAKSI PEKTIN DARI KULIT PISANG KEPOK (Musa paradisiaca) SECARA ENZIMATIS MENGGUNAKAN ENZIM SELULASE - Romansyah, Ryan Indra; Zaharah, Titin Anita; Ardiningsih, Puji (Tanjungpura University, 2026)
The utilization of banana peel waste for pectin extraction offers an alternative to reduce environmental waste while producing high-quality pectin that meets international standards at a minimal cost. This study aims to determine the optimal conditions (pH, enzyme concentration, temperature, and duration) for pectin extraction using cellulase enzymes and to characterize the resulting product. A factorial design method was employed. The optimum extraction conditions were determined using 0.05 g of cellulase at pH 5 and 50°C for 120 minutes, yielding a recovery of 10.40%. The extracted pectin is categorized as low-methoxyl pectin with a methoxyl content of 4.60% (below the 7.12% threshold). Characterization results showed an equivalent weight of 2.31 g, ash content of 2.03%, galacturonic acid content of 39.22%, and a degree of esterification of 66.58%.